2018
DOI: 10.1136/bmjopen-2017-019308
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical features of human metapneumovirus in hospitalised paediatric patients with acute respiratory illness: a cross-sectional study in Southern China, from 2013 to 2016

Abstract: ObjectivesHuman metapneumovirus (HMPV) is one of the most important respiratory viral pathogens affecting infants and children worldwide. Our study describes the epidemiological and clinical characteristics of HMPV present in patients hospitalised with acute respiratory illness (ARI) in Guangzhou, Southern China.Study designA cross-sectional study.SettingTwo tertiary hospitals in Guangzhou.Participants and methodsThroat swabs were collected over a 3-year period from 5133 paediatric patients (≤14 years) hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 51 publications
(36 reference statements)
8
32
0
Order By: Relevance
“…RSV, PIV, and HMPV are the most important respiratory viruses, causing lower respiratory illnesses among children worldwide [4][5][6]33]. In this study, RSV, PIV, and HMPV were the first (14.8%), sixth (4.4%), and ninth (2.8%) most frequently detected pathogens (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…RSV, PIV, and HMPV are the most important respiratory viruses, causing lower respiratory illnesses among children worldwide [4][5][6]33]. In this study, RSV, PIV, and HMPV were the first (14.8%), sixth (4.4%), and ninth (2.8%) most frequently detected pathogens (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Respiratory syncytial virus (RSV), parainfluenza virus (PIV), and human metapneumovirus (HMPV) are enveloped, nonsegmented, negative-sense, singlestranded RNA viruses belonging to the Paramyxoviridae family. These viruses are a significant cause of morbidity and mortality globally, especially among children in developing countries [1][2][3][4][5][6][7]. RSV is the most important pathogenic infection of childhood worldwide, causing a variety of manifestations from mild upper respiratory tract illnesses or otitis media to severe and potentially lifethreatening lower respiratory tract illnesses [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that most studies have focused on the epidemiological features of HMPV in the vulnerable population. For instance, Zhang and colleagues [15] performed a cross-sectional study in Guangzhou, and reported that 103 out of 5133 pediatric patients with ARIs (2.0%) were positive for HMPV. In the present study, 38 patients were positive for influenza virus infection, of which 68.4% were InfB infection, and the remaining were InfA infection.…”
Section: Discussionmentioning
confidence: 99%
“…16 Cough, rhinorrhea, wheeze, and fever are commonly reported symptoms in children infected with hMPV. [17][18][19][20][21][22] Virtually all children have evidence of exposure to hMPV by age 5 years. 15 hMPV is responsible for a significant portion (2%-12%) of respiratory tract infections 16,17,19,[23][24][25][26] and is associated with a large burden of hospitalizations and outpatient visits in younger children.…”
Section: Human Bocavirusmentioning
confidence: 99%